Correspondence between try-in pastes and resin cements, and color stability of bonded lithium disilicate disks - Rafael Soares Diniz; Letícia Fecury Bogéa de Albuquerque; Rudys de Jesus Rodolfo Tavarez; Eduardo Buozzi Moffa; Andréa Dias Neves Lago; Letícia Machado Gonçalves (Brazilian Oral Research)
Abstract: This study investigates the color correspondence of resin cements and try-in pastes, and the color stability of bonded lithium disilicate ceramic disks. Resin composite disks were fabricated (n = 36) to serve as the background for lithium disilicate disks prepared in two thicknesses (0.5 and 1.0 mm, n = 18 each). Two brands were used for try-in and cement procedures: Variolink Veneer and AllCem Veneer. For baseline, water was applied between the ceramic disks and their respective backgrounds to achieve the control group. This set was subjected to color measurement using an intraoral measurement device (T0). The try-in was inserted between background and ceramic, and this set was subjected to color measurement (T1). After adhesive procedures, the ceramic disk was placed under cement, and color measurement was performed with uncured cement (T2) and 24 h after light-curing (T3). Each set was immersed in distilled water and thermal-cycled, with color measurement being performed after 10,000 (T4) and 20,000 (T5) cycles. Color differences were calculated by CIELab (rEab) and CIEDE2000 (rE00). Data were analyzed by two-way ANOVA for repeated measurements and Tukey's test (α=5%). There was color correspondence of try-in and resin cement for the Variolink system, regardless of the ceramic thickness (p > 0.05). For the AllCem system, the thickness significantly influenced the color measurement (p < 0.001). The Variolink system also demonstrated color stability after 20,000 thermal cycles with rEab < 3.46 and rE00 < 2.25. It was concluded that the color correspondence between a try-in and its respective cement may vary according to resin cement composition.